An exploration of goal scoring strategies in an elite beach soccer tournament. Issue 3 (2nd July 2020) - Lastella, Michele; Escobar, Luiz; Lovell, Geoff P.; Scanlan, Aaron; Ellison, Elizabeth; McGowan, Lee; Guy, Joshua H.
ABSTRACT: Objectives: Despite the increasing popularity of beach soccer, few studies have examined goal scoring strategies during match-play. The aims of this study were to examine the different types of goals scored during an international tournament and determine what type of goals were associated with team performance. Methods: Twelve national teams were analysed across 52 matches in all phases of the 2018 European Beach Soccer League tournament. Observational data collection was conducted through video analysis of all 422 goals scored throughout the tournament. Results: Chi-square analyses revealed a significant difference in the type of goals scored x 2 (72) = 102, p = 0.01. Further, the amount of goals scored from a set-play were significantly higher than all other goal-scoring strategies ( p = 0.001). The amount of goals scored from goalkeeper-line defence were significantly lower than all other goal-scoring strategies ( p = 0.001). The percentage of goalkeeper-line goals was significantly related to total tournament points [F(2, 10) = 7.242, p = 0.023, R 2 = 0.42]. Conclusions: These data indicate that teams employing the goalkeeper-line strategy, where the goalkeeper plays outfield to serve as a numerical advantage, was associated with increases in scoring opportunities and team performance.